Seed endophytic bacterial profiling from wheat varieties of contrasting heat sensitivity - Aswini, Krishnan; Suman, Archna; Sharma, Pushpendra; Singh, Pradeep Kumar; Gond, Shrikant; Pathak, Devashish (Frontiers in Plant Science, 2023)
Wheat yield can be limited by many biotic and abiotic factors. Heat stress at the grain filling stage is a factor that reduces wheat production tremendously. The potential role of endophytic microorganisms in mitigating plant stress through various biomolecules like enzymes and growth hormones and also by improving plant nutrition has led to a more in-depth exploration of the plant microbiome for such functions. Hence, we devised this study to investigate the abundance and diversity of wheat seed endophytic bacteria (WSEB) from heatS (heat susceptible, GW322) and heatT (heat tolerant, HD3298 and HD3271) varieties by culturable and unculturable approaches. The results evidenced that the culturable diversity was higher in the heatS variety than in the heatT variety and Bacillus was found to be dominant among the 10 different bacterial genera identified. Though the WSEB population was higher in the heatS variety, a greater number of isolates from the heatT variety showed tolerance to higher temperatures (up to 55°C) along with PGP activities such as indole acetic acid (IAA) production and nutrient acquisition. Additionally, the metagenomic analysis of seed microbiota unveiled higher bacterial diversity, with a predominance of the phyla Proteobacteria covering >50% of OTUs, followed by Firmicutes and Actinobacteria. There were considerable variations in the abundance and diversity between heat sensitivity contrasting varieties, where notably more thermophilic bacterial OTUs were observed in the heatT samples, which could be attributed to conferring tolerance against heat stress. Furthermore, exploring the functional characteristics of culturable and unculturable microbiomes would provide more comprehensive information on improving plant growth and productivity for sustainable agriculture.